Gambaran Kesesuaian Peresepan Obat Pasien BPJS Rawat Jalan Dengan Formularium Nasional - Herty Nur Tanty; Siti Aisyah; Ida Diana; Anissa Nandya Kirana (Jurnal Farmasi IKIFA, 2023)
The hospital formulary is a list of drugs agreed upon by medical staff, compiled by the pharmacy and therapy committee set by the hospital director. With the formulary, pharmaceutical installations can provide drugs more efficiently and the drugs listed in the formulary must be guaranteed its availability. If a hospital does not have a hospital formulary, it will have an impact on the number of types of drugs, so that management is increasingly complex, and requires high costs because of the magnitude of the risks that must be borne. The risks that must be experienced are storage costs, booking costs, damage costs, higher number of expired drugs and the possibility of patients getting drugs that are not optimal in doctor's prescribing, impacting by decreased quality and quality of health service. This research aims to find out the description of the suitability of prescription writing with hospital formulary on outpatient general patients in the Hospital "X" in North Jakarta for the period of January- March 2021. This research belongs to a type of non-experimental research that is quantitative descriptive. Data is collected retrospectively. The analysis period of 3 months, the calculation of samples using the Slovin formula and data collection using the systematic random sampling method, i.e., by determining the interval for the January-March 2021 prescription taken as a sample, so that it can be known which prescription does not match with the hospital formulary "X" in January-March 2021. The research uses a secondary data collection technique, namely prescription sheets from January to March 2021. Based on the Decree of the Minister of Health of the Republic of Indonesia Number 129 of 2008 on Hospital Minimum Service Standards mentioned that the standard of writing prescriptions in accordance with formulary is 100%. From the research that has been done it can be concluded that the percentage of suitability of prescriptions writing on outpatient general patients to hospital formulary "X" in January 2021 is 95.45%. In February 2021, it is 96.01%, and in March 2021, it is 96.01%. In 3 months, the average percentage of suitability of prescription writing in outpatient general patients to hospital formulary "X" is 95.83%.